2015
DOI: 10.1111/nuf.12122
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Life Planning: A Concept Analysis

Abstract: A reproductive life plan can serve as a framework for promoting reproductive health across the life span of both men and women. Healthcare providers must assess the individual's ability to understand and utilize educational resources to ensure full and effective participation in reproductive life planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…It is further considered that the decision making regarding contraception may be misleading due to lack of knowledge of the own contraceptive methods risks, reinforcing the need for guidance and health education. 5,8 Significant number of pregnancies confirmed as intended were not planned sand result from ambiguity and fatalism. It was verified that in women who stated they had no desire to become pregnant and others who did not want a pregnancy in the next year of their lives, more than half were at risk of unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is further considered that the decision making regarding contraception may be misleading due to lack of knowledge of the own contraceptive methods risks, reinforcing the need for guidance and health education. 5,8 Significant number of pregnancies confirmed as intended were not planned sand result from ambiguity and fatalism. It was verified that in women who stated they had no desire to become pregnant and others who did not want a pregnancy in the next year of their lives, more than half were at risk of unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It was verified that in women who stated they had no desire to become pregnant and others who did not want a pregnancy in the next year of their lives, more than half were at risk of unintended pregnancy. 8 In Brazil, data from the National Survey on Childbirth and Birth indicate that 56% of women had not planned the pregnancy and of the total of interviewed, 25% had the pregnancy classified as at risk. 19 In this prerogative, one questions the woman´s path in the care lines considering the interpregnancy interval of the participants in average of five years, in addition to the previous knowledge of heart disease in all pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of publications between 2000 and 2014 about the RLP concept suggested that reproductive life planning was integral to preconception care and family planning and could serve as a framework for promoting reproductive health across the lifespan of both men and women [8].…”
Section: Introductionmentioning
confidence: 99%